2020
DOI: 10.1002/cam4.3580
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of radiation interruption in different periods for nasopharyngeal carcinoma patients in the intensity‐modulated radiation therapy era

Abstract: We aimed to investigate the prognostic value of radiation interruptions at different times on the overall survival (OS) and disease‐free survival (DFS) of patients with nasopharyngeal carcinoma receiving intensity‐modulated radiation therapy. Totally, 4510 patients were identified from a well‐established big‐data intelligence platform. Optimal interruption thresholds were identified using Recursive partitioning analyses. Actuarial rates were plotted using the Kaplan–Meier method and were compared using the log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…31 The observation that the number of radiotherapy interruptions were similar in patients receiving NGT and PEG is of particular interest and significance considering their well-known detrimental effect on midrange and long-term survival. 32,33 The better swallow outcomes observed with the use of NGT in most of the studies are an important consideration in choosing the timing and method of providing nutrition support in patients with receiving CRT. In fact, long-term swallow function is a major factor influencing quality of life in survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The observation that the number of radiotherapy interruptions were similar in patients receiving NGT and PEG is of particular interest and significance considering their well-known detrimental effect on midrange and long-term survival. 32,33 The better swallow outcomes observed with the use of NGT in most of the studies are an important consideration in choosing the timing and method of providing nutrition support in patients with receiving CRT. In fact, long-term swallow function is a major factor influencing quality of life in survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the number of radiotherapy interruptions were similar in patients receiving NGT and PEG is of particular interest and significance considering their well‐known detrimental effect on midrange and long‐term survival 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…75.1%, p=0.006) were significantly detrimental to DFS and OS. In the further multifactorial analysis, interruptions longer than 3 or 4 days afterwards were both poor prognostic factors ( 57 ). Certainly, it has been reported that the prolongation of the treatment time has no effect on the prognosis of the patients ( 57 ).…”
Section: Interruption Of Radiotherapymentioning
confidence: 99%
“…More specifically, ~20% of these patients suffer from acute severe radiation-induced injuries, which often cause uncontrollable pain, resulting in treatment interruptions (8,9). These interruptions eventually lead to failure of tumor control, thereby shortening the overall survival time (10,11). However, the lack of sensitive and specific biomarkers makes it difficult to predict the occurrence of acute severe radiation-induced injury in patients.…”
Section: Introductionmentioning
confidence: 99%